O que e como dizem mulheres autoras de obras integrantes do PNLD literário 2023 - Mezacasa, Lívia Berro (My University, 2025)
This dissertation focuses on the composition of the literary book selected by the 2023 PNLD Literary Program and deals with works written and illustrated by women. The research is part of the activities of the research group Observatório de Leitura e Literatura (OLLI-UCS/CNPq) and is situated in the field of Education, specifically in the research line Educational processes, language, technology and inclusion. The objective of the dissertation is to investigate the themes and modes of expression explored in these works, and how they are discursively organized as artistic objects in order to contribute to the promotion of literary and aesthetic education in the early years of Elementary School. In addition to literary works, legal documents of the Program - such as the public notice and evaluation form - were analyzed in order to identify the conceptions present in the documents regarding children's literature that guide the selection of works, as well as the artistic treatment directed towards the submitted works. As theoretical basis, it is used, primarily, studies by Lajolo and Zilberman (2017, 2022), and Arroyo (1968) on children's literature; Zilberman (2003) on the presence of children's literature in schools; Barthes (2004) and Candido (2012) on literature and reading; and Showalter (1994) on literature by female authors. As a methodological basis, Content Analysis was adapted to the research corpus. The analysis started with the examination of Public Notice No. 01/2021, followed by a discussion of the evaluation form in light of the nature of the object to be selected - literary works for children in the early years of Elementary School. After analyzing these documents, based on predefined criteria, 11 works written and illustrated by women were selected and presented. Finally, an exploratory study was conducted to explore three works that share common elements in their composition; also, aspects that reflect traces of female authorship were sought. The relevance of this research is justified by focusing on the collection of literary works that reach the Brazilian public schools and by examining female authorship, as well as by the potential to conduct a study that emphasizes the artistic and aesthetic dimensions within education. Following the reflections on the corpus, the findings highlight the importance of including children's literature written and illustrated by women in the PNLD collection. The works studied feature characters with emancipatory conduct, rich literary language, sensitivity in addressing themes within the narrative, and modes of expression. Traces of authorship are subtle in the works, showing unique ways of writing and illustrating, revealing characteristics of femininity. [resumo fornecido pelo autor]
Esta dissertação atenta para a composição do livro literário selecionado pelo PNLD Literário 2023 e ocupa-se de obras escritas e ilustradas por mulheres. A pesquisa integra ações do grupo de pesquisa Observatório de Leitura e Literatura (OLLI-UCS/CNPq) e situa-se no campo da Educação, na linha de pesquisa Processos educacionais, linguagem, tecnologia e inclusão. O objetivo da dissertação é investigar temáticas e modos de dizer que são explorados nessas obras e como as mesmas se organizam discursivamente como objetos artísticos de modo a contribuir para a promoção da educação literária e estética nos anos iniciais do Ensino Fundamental. Além de obras literárias, foram analisados documentos legais do Programa - edital e ficha de avaliação -, a fim de identificar concepções presentes nos documentos acerca de literatura infantil que norteiam a seleção das obras, bem como qual o tratamento artístico direcionado às obras inscritas. Utiliza-se como base teórica, especialmente, estudos de Lajolo e Zilberman (2017, 2022) e Arroyo (1968) acerca de literatura infantil; Zilberman (2003) no tocante à presença da literatura infantil na escola; Barthes (2004) e Candido (2012) sobre literatura e leitura; e Showalter (1994) sobre literatura de autoria feminina. Como base metodológica, a Análise de Conteúdo foi ajustada ao corpus da pesquisa. Partiu-se da análise do Edital nº01/2021, na sequência, problematizamos a ficha à luz da natureza do objeto a ser selecionado - obras literárias para crianças dos anos iniciais do Ensino Fundamental. Após a análise desses documentos, com base em critérios previamente definidos, foram selecionadas e apresentadas 11 obras escritas e ilustradas por mulheres. Por fim, foi desenvolvida pesquisa exploratória, a fim de adentrar em três obras que possuem elementos comuns na sua constituição e ainda buscaram-se elementos que apontassem traços da autoria feminina. A relevância da pesquisa justifica-se por privilegiar acervo de obras literárias que chegam às escolas públicas brasileiras e pelo olhar da investigação recair sobre autoria feminina, bem como pela possibilidade de efetuar estudo que privilegie as dimensões artística e estética no âmbito da educação. Realizadas as reflexões acerca do corpus, aponta-se como resultados a relevância na composição de acervos da presença de literatura infantil escrita e ilustrada por mulheres no PNLD. As obras estudadas têm personagens com conduta emancipatória, linguagem literária rica, sensibilidade no tratamento de temáticas presentes na narrativa e modo de dizer. Marcas da autoria são sutis nas obras e mostram modos peculiares de escrever e de ilustrar, evidenciando características do feminino. [resumo fornecido pelo autor]
Keywords: Programa Nacional do Livro Didático (Brasil); Mulheres na literatura; Literatura infantil; Ensino fundamental; National Textbook Program (Brazil); Women in literature; Children's literature; Elementary school